2007
DOI: 10.1111/j.1600-0765.2007.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin expression in periodontal disease

Abstract: The results obtained from this study suggest that melatonin could act as a protective function in fighting periodontal infection. However, further studies in this area are encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 45 publications
5
72
0
1
Order By: Relevance
“…This study also reported that the melatonin levels in saliva and gingival crevicular fluid were similar (with no significant differences), confirming the results obtained in previous studies [62]. In the study carried out by Gómez-Moreno [63], the authors found that patients with periodontal disease had a significantly lower plasma and salivary level of melatonin, maintaining a similar salivary/plasma melatonin ratio to that of the healthy subjects.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This study also reported that the melatonin levels in saliva and gingival crevicular fluid were similar (with no significant differences), confirming the results obtained in previous studies [62]. In the study carried out by Gómez-Moreno [63], the authors found that patients with periodontal disease had a significantly lower plasma and salivary level of melatonin, maintaining a similar salivary/plasma melatonin ratio to that of the healthy subjects.…”
Section: Resultssupporting
confidence: 89%
“…The authors explained this as a consequence of the oral inflammatory mediators. In the remaining studies, the correlation between salivary melatonin levels and periodontal disease was negative [61,62,63]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis is a chronic inflammatory disease caused by dental plaque microorganisms, and is characterized by the destruction of supporting tissues (bone and connective tissue) and loss of teeth (1,2). The progression of periodontal disease depends on the host's response to the bacteria and bacterial products, and this often leads to systemic inflammation (3).…”
Section: Introductionmentioning
confidence: 99%
“…Many of its effects differ to its primary neurohormonal functions and are due to its anti-inflammatory properties, its ability to be an effective freeradical scavenger and for the stimulation of several antioxidant enzymes (Allegra et al, 2003;Czesnikiewicz-Guzik et al, 2007). In response to the inflammation of periodontal disease, increased levels of plasma melatonin may be induced, leading to an increase in salivary melatonin, where this indoleamine may exert a protective role during the periodontal inflammatory process due to its anti-inflammatory and anti-oxidant effects (G omez-Moreno et al, 2007;G omez-Florit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%